Early Screening of Diabetes Mellitus Through Blood Glucose Level Examination - Alfian Rajab; Rindani Claurita Toban; Rusli Taher; Mulyati (CV. Paperhome Indonesia, 2026)
Early detection of non-communicable diseases is essential to reduce the growing burden of diabetes mellitus and hypertension at the community level. This study aimed to identify individuals at risk through a community-based health screening program conducted at Graha Mas Residence. A descriptive observational design was applied. Twelve adult participants voluntarily underwent structured anamnesis, systolic blood pressure measurement, and random blood glucose (RBG) testing using a standard glucometer. Data were analyzed descriptively using frequency and percentage distributions. The results showed that 4 participants (33.3%) had RBG levels >150 mg/dl, while 5 participants (41.7%) had systolic blood pressure >140 mmHg. These findings indicate the presence of individuals at potential risk for metabolic and cardiovascular disorders within the community. Elevated random blood glucose levels suggest the need for further confirmatory testing, such as fasting plasma glucose or HbA1c measurement. Meanwhile, increased systolic blood pressure highlights the importance of early hypertension detection and management to prevent future cardiovascular complications. Although the sample size was limited, the proportion of abnormal findings underscores the relevance of community-based screening as a preventive strategy. Early identification allows timely health education, lifestyle modification, and referral to appropriate health services. Integrating routine screening with promotive and preventive interventions may contribute significantly to reducing the incidence and complications of diabetes and hypertension. In conclusion, community health screening is a feasible and practical approach for early risk detection of non-communicable diseases. Strengthening such programs at the local level may support broader public health efforts in controlling metabolic and cardiovascular risk factors.